The impact of TikTok livestreaming on buying behavior in fashion products of Gen Z in Vietnam - Nguyen, Thi Thuy Dung; Stříteský, Václav; Machek, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis aims to evaluate the influence of TikTok's live-stream platform on the purchase behavior of young generations in Vietnam in the fashion industry. And investigate how TikTok live-streamming affects the preferences, purchase decisions, and engagement of target demographic with fashion products. In terms of academia, it improves the rapidly developing field of consumer behavior in social commerce by promoting further study. Businesses and marketers targeting Generation Z in Vietnam can benefit from the study's valuable insights, the research deeply shows the factors that lead to purchase decisions in the clothing category of young generation. Therefore, businesses tailor their marketing strategies to maximize their appeal to this demographic. The primary data was collected by quantitative method to find the relationship between customer’s buying behavior, represented by purchased intention, and other characteristics of TikTok platforms. An online survey was conducted by Google Docs to collect data from 319 respondents who are active TikTok’s users in Vietnam. The findings indicated that all six independent variables have positive impact to the customer purchase intention. The study discovers the specific ways how TikTok's livestreaming influences the fashion buying behavior of Gen Z in Vietnam. Expected results will demonstrate TikTok's potential as a marketing channel to identify key trends, preferences, and factors that contribute to the effectiveness of TikTok as a platform for fashion commerce in Vietnam.
Vedoucí práce: Václav Stříteský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses